Chronic Infection in Recurrent Pregnancy Loss - Fuminori Kimura (Fertility & Reproduction, 2023)
In the present study, the effects of chronic endometritis (CE) on implantation and pregnancy outcomes, the effects of CE on endometrial function, and the effects of progesterone as a treatment for CE were examined. It was found that the pregnancy rate and live birth rate were significantly lower in CE patients in a prospective study. When patients were diagnosed with CE, not only were the pregnancy rate and live birth rate significantly lower, but the miscarriage rate was higher in a retrospective study. Next, the presence of chronic deciduitis (CD) in the miscarriage specimen was determined in patients diagnosed with or without CE before pregnancy. CD was determined when the presence of clusters of plasma cells or five or more plasma cells in the decidua. CD was found in more than half of CE, but not found in Non-CE before pregnancy. In in vitro study, we revealed the secretions of TNF[Formula: see text], IL1[Formula: see text], and IL6 per cell were significantly higher in CE. The rate of Th1 was greater and it of Th2 was significantly lower in CE, and those of Tregs and Th17 were not different. Both PRL and IGFBP1, decidualized markers, showed significant decreases in secretion with CE, and conversely, the number of cells was significantly higher in the CE group. Based on the results of bench studies, we hypothesized that an altered administration route and increased dosage of progestogen may improve clinical outcomes. The clinical outcomes of patients who underwent single frozen-thawed blastocyst transfer were examined for each hormone replacement therapy. It was found that using a progesterone vaginal suppository in combination with an oral progestin for hormone replacement improved the live birth rate, but not the miscarriage rate in CE patients when compared with using an oral progestin alone.